An approach of intelligent searching of information in texts - Chebanuyk, O.V. (Проблеми програмування, 2022)
Paper proposes an approach aimed at question oriented searching of information in texts. Texts are parsed, keywords and extra features of questions are marked, and sentences in text with the most relevant information to question are defined. Proposed approach is applied to Cyrillic and Latin languages. Case study illustrates how to obtain answers to questions about Bulgarian fairytale that is represented on different languages (Bulgarian and English). Evaluation of the proposed approach is introduced. Description of the software architecture and source code of the corresponding software system are represented. Data structures and examples of *.xml files for storing information about question and answers are outlined. У роботі представлено методику пошуку інформації в текстах на запит. Тексти аналізуються, визначаються ключові слова та додаткові характеристики запитань, потім, у тексті шукаються речення з найбільш релевантною інформацією щодо запитання. Запропонована матодика застосовується до мов, що використовують як кирилицю так і латиницю. У прикладі показано, як отримати відповіді на запитання про болгарську казку, яка представлена різними мовами (болгарською та англійською). У роботі представлено оцінювання запропонованого підходу. Представлено опис архітектури програмного забезпечення та вихідного коду відповідної програмної системи. Описано структури даних та приклади *.xml файлів для зберігання інформації про запитання та відповіді.